ANALISIS MANAJEMEN KELAS PADA KURIKULUM MERDEKA BELAJAR DI SEKOLAH DASAR NEGERI 28 MANCANI KECAMATAN TELLUWANUA KOTA PALOPO - Iqwana Ummul Fatimah; Hisban Thaha; Muhammad Guntur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the form of classroom management in the independent learning curriculum at State Elementary School 28 Mancani, Telluwanua District, Palopo City. In the study entitled Analysis of classroom management in the independent learning curriculum at State Elementary School 28 Mancani, Telluwanua District, Palopo City, a descriptive approach is applied. The primary data in this study are data related to Class Management in the Independent Learning Curriculum at State Elementary School 28 Mancani, Telluwanua District, Palopo City. Data collection techniques used for data collection include direct observation, interviews with related parties, as well as site visits and discussions to obtain the necessary information. In addition, documentation techniques are used to collect data from various written sources, visuals, or important works from individuals. Research results 1. The implementation of classroom management in the independent learning curriculum at State Elementary School 28 Mancani, Telluwanua District, Palopo City is fully implemented in accordance with the 4 stages of management implementation according to George R Tarry, namely the Planning Stage, Organizing, Actuating and Controlling. 2. Challenges and opportunities for teachers in implementing classroom management in the independent learning curriculum at SDN 28 Mancani, Telluwanua District, Palopo City are seen from several sides, namely 1) Challenges related to the diversity of student backgrounds, characteristics, and learning styles. Opportunities to implement more creative, inclusive, and differentiated learning approaches. 2) Challenges related to limited human resources. Opportunities to improve adaptability competencies in managing classes. 3) Challenges to optimize continuous monitoring of learning quality. Opportunities to build a culture of reflection, collaboration, innovative learning practices, and improve learning quality.